Predictors of rural driver self-reported passing behaviors when interacting with farm equipment on the roadway - Amir Ghanbari; Cara Hamann; Stephanie Jansson; Michelle Reyes; Kayla Faust; Joseph Cavanaugh; Natoshia Askelson; Corinne Peek-Asa (Transportation Research Interdisciplinary Perspectives, 2023)
Background: Crashes involving farm equipment (FE) are a major safety concern for farmers as well as all other users of the public road system in both rural and urban areas. These crashes often involve passenger vehicle drivers striking the farm equipment from behind or attempting to pass, but little is known about drivers’ perceived norms and self-reported passing behaviors. The objective of this study is to examine factors influencing drivers' farm equipment passing frequencies and their perceptions about the passing behaviors of other drivers. Methods: Data were collected via intercept surveys with adult drivers at local gas stations in two small rural towns in Iowa. The survey asked drivers about their demographic information, frequency of passing farm equipment, and perceptions of other drivers' passing behavior in their community and state when approaching farm equipment (proximal and distal descriptive norms). A multinomial logistic regression model was used to estimate the relationship between descriptive norms and self-reported passing behavior. Results: Survey data from 201 adult drivers showed that only 10% of respondents considered farm equipment crashes to be a top road safety concern. Respondents who perceived others passing farm equipment frequently in their community were more likely to report that they also frequently pass farm equipment. The results also showed interactions between gender and experience operating farm equipment in terms of self-reported passing behavior. Conclusions/implications: Results from this study suggest local and state-level norms and perceptions of those norms may be important targets for intervention to improve individual driving behaviors around farm equipment.